Learning in a Disrupted Environment: Exploring higher education student resilience using the Dynamic Interactive Model of Resilience (Journal of Applied Learning and Teaching, 2023)
The coronavirus pandemic brought unprecedented circumstances, providing insights into how systems (people, institutions and societies) cope during a disruption. This paper reports research undertaken at one university in the South West of England, which adopted a mixed-methods approach to investigate how students responded to and coped with the impact of Covid-19 disruption and what they perceived as influencing their resilience.Data were gathered from 434 students (undergraduate and postgraduate) using an online survey. Twenty of these students were subsequently interviewed individually. Data analysis used the lens provided by the Dynamic Interactive Model of Resilience (DIMoR) to explore the complexity of resilience and how it is shaped and impacted by internal and surrounding environments for any given system.The research revealed the value of DIMoR as a tool for analysis and highlighted the dynamic, interactive and multifaceted nature of resilience as something that is influenced by multiple other systems rather than being a static quality within a system. A range of impacting risk/protective factors and vulnerabilities/invulnerabilities were identified, which are not either/or but fluctuate and exist to a greater or lesser degree depending on context and influences. The research also showed the shifting nature of surrounding systems that can become more or less proximal and influential depending on circumstance. Additionally, the study provided insight into the overriding importance of proximal relationships and the role lecturers/tutors can play in helping students to access university support services. Wider implications of the findings are discussed in relation to university processes and practices.